Sob a Torre de Marfim : A Escola Técnica Redentorista, um lugar de memórias, estratégias e práticas de gênero em Campina Grande- PB, (1975-1985). - Bélens, Jussara Natália Moreira (2013)
This thesis analyzes the gender subjectivities constructed between strategies of disciplinary power in the Technique School Redentorista- ETER, at Campina Grande - PB, among the years of 1975-1985, and the daily practices of pupils, teachers and professors who used to resignify in many ways the devices and the operators of control and pertaining to school regulation. The ETER was in the years of 1975-1985 a place of technic-professional education of manufacture of different subjectivities of gender, qualified for the new professional activities in ascension, in that historical and cultural configuration. The gender subjectivities, woven there, in some way, resized, in this city, still predominant sexists ideas that separated and opposed the places of education in level technician and college for men and women. Based in the Educational Reformation promulgated by the Law Nº 5,692/71, the ETER resized the educational philosophy, passing of masculine vocational seminary for a mixing school, among the decades of 1960 and 1970 and, later, in the year of 1975, for the Technique School Redentorista, under the motto of Educate To free . It started to offer the technician course in Electronics and Telecommunications for young women and poor youngsters of the city. The objective is to argue as the young students subjetivated the values repassed for the education that crossed values of the ability and the personal merit, spread out for the curricular structure, based in the technicality and humanists values, spread out for the pedagogical tactics in some disciplines and the pertaining to school activities creating, thus, in ETER, a familiar ambience and of friendship, present in the memory of the narrator. By means of the reading of documentation of the proper school (fiches of school registration of pupils, photo albums), the profile of the young students was arisen; we search in the periodicals A União and the Diário da Borborema, in the years cut for study, as the women participated of the spaces of education in this city, since this started to be synonymous of modernity/urban development; and from verbal history, knew different practices of women pupils and men pupils of ETER in the processes of subjectivation of the practical formation proposed by ETER. Unveiling via the practical memories of the daily ones of former-pupils and the microfreedoms lived by them to the history of the education of ETER, the thesis verifies as social place that the developmentalist military State and the catholic church, through the emblematic figure of the redentorista priest Edelzino Pitiá, exercised the desire of power and control of behaviors and feelings, shaping, thus, productive gender subjectivities with sight to education for the work and education for freedon.